5y(2y-4)+14y=

Simple and best practice solution for 5y(2y-4)+14y= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5y(2y-4)+14y= equation:


Simplifying
5y(2y + -4) + 14y = 0

Reorder the terms:
5y(-4 + 2y) + 14y = 0
(-4 * 5y + 2y * 5y) + 14y = 0
(-20y + 10y2) + 14y = 0

Reorder the terms:
-20y + 14y + 10y2 = 0

Combine like terms: -20y + 14y = -6y
-6y + 10y2 = 0

Solving
-6y + 10y2 = 0

Solving for variable 'y'.

Factor out the Greatest Common Factor (GCF), '2y'.
2y(-3 + 5y) = 0

Ignore the factor 2.

Subproblem 1

Set the factor 'y' equal to zero and attempt to solve: Simplifying y = 0 Solving y = 0 Move all terms containing y to the left, all other terms to the right. Simplifying y = 0

Subproblem 2

Set the factor '(-3 + 5y)' equal to zero and attempt to solve: Simplifying -3 + 5y = 0 Solving -3 + 5y = 0 Move all terms containing y to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 5y = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 5y = 0 + 3 5y = 0 + 3 Combine like terms: 0 + 3 = 3 5y = 3 Divide each side by '5'. y = 0.6 Simplifying y = 0.6

Solution

y = {0, 0.6}

See similar equations:

| 9a-3(a+3)= | | 8c-10c-6=10 | | -1a-24=5a | | 2x+7(8+2x)=8 | | 6(4y+5z)-30z= | | 4log(x-6)=11 | | 16h-13h-2h-1=15 | | (25.12^2)/4(3.14) | | 52=12+4w | | -7/9(x-y+36) | | 2c-c=14 | | (80x-54y)-(62x+9y)= | | 8y-y+2y=18 | | 5(2y+4z)-20z= | | 15+3y=25 | | 4x-5/3x | | 6y(3y-4)+22y= | | (11x+23y)+(38x+50y)= | | -(2x^2-7x+7)= | | 4y(3y-6)+19y= | | A=8*(3.14) | | 4x-6=4(x+5) | | (63x+45y)-(13x+40y)= | | 6(x-6)+20=2(x-6) | | -(12b-10)+5(3b-2)= | | 8x+3=-3+3x+21 | | (23x+64y)+(33x-16y)= | | 4a-2(a+6)= | | a/3=7/10 | | (43x+60y)+(38x-23y)= | | (79x+76y)-(16x+40y)= | | -3x-13=6x+23 |

Equations solver categories